A MORPHOLOGICAL ANALYSIS OF WORD FORMATION PROCESS IN MOVIE SCRIPT “THE FLASH” - Devany, Almira; Sopha, Diana (PHILOLOGY Journal of English Language and Literature, 2024)
This study aims to identify the types of word formation processes that appear in the movie script “The Flash” and then to find out the dominant type in the data. The process of word formation is one of the important things to analyze because without realizing it often occurs in daily conversations, as well as in the conversation of a movie. This research uses a qualitative research method. The data used in The Movie script “The Flash” Season 1 Episode 1 "Pilot" consists of 61 script pages. In this study, there are several types used by researcher to collect and analyze data, including reading the script, identifying words, classification based on types of word formation process, describing data, and finally making conclusions. The results of this study show that there are 10 types of word formation process based on Yule’s theory. Researcher found 156 words from 6 types of word formation process and 4 other types were not found, including derivation (prefix, infix, suffix) 60 words (93,6), compounding 46 words (71,76%), blending 36 words (56,16%), back-formation 6 words (9,36%), acronym 6 words (9,36%), clipping 2 words (3,12%). Coinage, borrowing, conversion, and multiple process are not found in the data. Based on calculations, the researcher concluded that derivation is the dominant type of word formation that appears in The Movie Script “The Flash”.